Performance of grid-connected solar photovoltaic power plants in the Middle East and North Africa - Jalal Assadeg; Kamaruzzaman Sopian; Ahmad Fudholi (Institute of Advanced Engineering and Science, 2019)
A conceptual design Study of a solar electrical power system using PV array for a 5.3MW as nominal power required is presented. A Bird model has been used to estimate hourly, daily, monthly and yearly solar radiation amounts. f-f-chart is a design method was chosen to simulate the fraction of the solar energy required for the load given the PV array areas and climatic conditions. Four cities in the Middle East and North Africa representing different locations at southern Mediterranean region are selected Tripoli, Alexandria, Tunisia and Gaza city. Tripoli City has the best performance for 73% of nominal Power followed by Alexandria about 66% and then Gaza around 63%, Tunisia City has lowest solar fraction about 59% according to the Monthly and annual solar fraction Data.